From 11:00PM PDT on Friday, July 1 until 5:00AM PDT on Saturday, July 2, the Shmoop engineering elves will be making tweaks and improvements to the site. That means Shmoop will be unavailable for use during that time. Thanks for your patience!
The first step is to simplify the expression on either side of the equation:
x + 3 = 12
Now, we solve as we did earlier:
Solve the equation z – 6 = 5.
If we write z = 5, we've made the quantity on the left heavier by 6 but haven't made the quantity on the right heavier at all. Uh-oh—the scale's a-tippin'. To correctly solve the equation, we need to change each quantity by the same amount. We add 6 to the expression z – 6 and also add 6 to 5 to get:
z – 6 + 6 = 5 + 6 z = 11
Solve the equation 9 – 8 + 2 = x + 4.
First, simplify the expression on each side of the equation: